Composition of main and bycatch in the drift net gear at PPI Air Bangis - Fitriani, Rada; Brown, Arthur; Nofrizal, Nofrizal (Science, Technology, and Education Care, 2025)
With 72.56 km of coastline, Air Bangis is one of the largest fish producers in West Pasaman. West Sumatra has a vast marine area with hundreds of islands running north to south. At PPI Air Bangis, drift gillnets are used in the Pangkalan and Pini areas. Pangkalan Island is about 7 miles away, and Pini Island is 60 miles away. The fishing grounds greatly influence the amount of catch, what variables affect the catch in different fishing grounds, and what types of catch are caught in different fishing grounds. The method used was direct interviews in the fishing waters to classify the types of species and count the number of species caught by the drift gillnet gear. Fishermen were also interviewed to determine the standard main and bycatch. These results were analyzed using descriptive statistical analysis and tabulated in tables and graphs. Overall, the number of species caught by drift gillnet gear. Site distance, vessel capacity, and water conditions greatly influenced the effectiveness of the fishing grounds. In 6 GT vessels, the highest main catch was 58%, and the highest bycatch was 42%. On 3 GT vessels, the highest main catch was 57%, and bycatch was 43%. To maximize fish catch, proper and planned selection of fishing sites is essential while considering external factors such as selectivity of fishing gear used and weather conditions. Thus, tools such as echosounder can greatly help fishermen locate where fish congregate